2018
DOI: 10.4028/www.scientific.net/kem.792.160
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Axially Loaded Concrete Filled Steel Tube Elements of Self-Stressing Concrete

Abstract: This work is dedicated to an experimental research of strength and resistance characteristics of axially loaded concrete filled steel tube elements of self-stressing concrete, including high-performance concrete. Labcrete specimens of circular section 112 mm in diameter and 1000 mm in length were used in experiments. The research shows that the use of self-stressing concrete increased the strength of the specimens by approximately 10%, and enhanced elastic behavior limit by 20-33%. In the course of testing sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Krishan and A.I. Sagadatov [31][32][33]. The compa experimental data for two series of columns with an outer diameter of the of 159 and 219 mm and wall thickness of 6 and 8 mm, can be introduced re Also, the developed methodology and software was tested on experimental data presented in the works of A.L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Krishan and A.I. Sagadatov [31][32][33]. The compa experimental data for two series of columns with an outer diameter of the of 159 and 219 mm and wall thickness of 6 and 8 mm, can be introduced re Also, the developed methodology and software was tested on experimental data presented in the works of A.L.…”
Section: Resultsmentioning
confidence: 99%
“…Krishan and A.I. Sagadatov [31][32][33]. The comparison with the experimental data for two series of columns with an outer diameter of the concrete core of 159 and 219 mm and wall thickness of 6 and 8 mm, can be introduced respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To solve this problem, scholars have found that the bearing capacity of CFST structure can be significantly improved by filling self-stressing concrete (SC) into steel tube to form self-stressing concrete-filled steel tube (SCFST) structure. [14][15][16][17][18] However, although the SCFST structure solves the void defects of the ordinary CFST, the SC is expensive to use, difficult to make, and requires a high maintenance environment. Besides, the uneven distribution of self-stress may reduce the deformation capacity of CFST columns.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the separation problem between core concrete and steel tube, the interaction of CFST structure is often weakened in actual engineering. To solve this problem, scholars have found that the bearing capacity of CFST structure can be significantly improved by filling self‐stressing concrete (SC) into steel tube to form self‐stressing concrete‐filled steel tube (SCFST) structure 14–18 . However, although the SCFST structure solves the void defects of the ordinary CFST, the SC is expensive to use, difficult to make, and requires a high maintenance environment.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 21 conducted the push-out tests on self-stressing concrete filled steel tubular (SCFST) columns and showed that the bond strength of specimens was obviously higher than that of ordinary CFST. Krishan et al 22 indicated that the use of selfstressing concrete increased the strength of specimens by approximately 10%, and enhanced the elastic behavior by 20%~33%. Tam et al 23 revealed that the deformation capacity and ultimate stress of recycled CFST under eccentric compression increased and decreased with the appropriate increase of expansive agent.…”
Section: Introductionmentioning
confidence: 99%